An evidence-based review of the use of vasoactive and inotropic medications in post-operative paediatric patients after cardiac surgery with cardiopulmonary bypass from 2000 to 2020. (20th December 2020) - King, Caitlin E.; Thompson, Elizabeth J.; Foote, Henry P.; Zimmerman, Kanecia O.; Hill, Kevin D.; Chamberlain, Reid; Hornik, Christoph P.
Abstract: Background: Infants with moderate-to-severe CHD frequently undergo cardiopulmonary bypass surgery in childhood. Morbidity and mortality are highest in those who develop post-operative low cardiac output syndrome. Vasoactive and inotropic medications are mainstays of treatment for these children, despite limited evidence supporting their use. Methods: To help inform clinical practice, as well as the conduct of future trials, we performed a systematic review of existing literature on inotropes and vasoactives in children after cardiac surgery using the PubMed and EMBASE databases. We included studies from 2000 to 2020, and the patient population was defined as birth – 18 years of age. Two reviewers independently reviewed studies to determine final eligibility. Results: The final analysis included 37 papers. Collectively, selected studies reported on 12 different vasoactive and inotropic medications in 2856 children. Overall evidence supporting the use of these drugs in children after cardiopulmonary bypass was limited. The majority of studies were small with 30/37 (81%) enrolling less than 100 patients, 29/37 (78%) were not randomised, and safety and efficacy endpoints differed widely, limiting the ability to combine data for meta-analyses. Conclusion: Vasoactive and inotropic support remain critical parts of post-operative care for children after cardiopulmonary bypass surgery. There is a paucity of data for the selection and dosing of vasoactives and inotropes for these patients. Despite the knowledge gaps that remain, numerous recent innovations create opportunities to rethink the conduct of clinical trials in this high-risk population.